Some design considerations for polymer-free drug-eluting stents: A mathematical approach. (May 2015) - McGinty, Sean; Vo, Tuoi T.N.; Meere, Martin; McKee, Sean; McCormick, Christopher
Graphical abstract: Abstract: In this paper we provide the first model of drug elution from polymer-free arterial drug-eluting stents. The generalised model is capable of predicting drug release from a number of polymer-free systems including those that exhibit nanoporous, nanotubular and smooth surfaces. We derive analytical solutions which allow us to easily determine the important parameters that control drug release. Drug release profiles are provided, and we offer design recommendations so that the release profile may be tailored to achieve the desired outcome. The models presented here are not specific to drug-eluting stents and may also be applied to other biomedical implants that use nanoporous surfaces to release a drug.